2020
DOI: 10.1093/geront/gnz188
|View full text |Cite
|
Sign up to set email alerts
|

“They’re in My Heart, Mind, and Cells”: What Continuing Bonds Reveal About Social Networks

Abstract: Background and Objectives Research suggests that robust social networks have positive effects on peoples’ well-being. An instrumental methodology for studying networks is the social convoy model, a diagram of concentric circles that illustrate network size, structure, and satisfaction. Convoys have been described as dynamic. Specifically, as people age, their convoys become stronger and smaller due to focusing on what matters most and accumulating losses. Therefore, convoys only include meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Wang & Hu, 2019). This study found that a robust social network for Shiduer should include a self-support group and other kinship and friends (Stemen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Wang & Hu, 2019). This study found that a robust social network for Shiduer should include a self-support group and other kinship and friends (Stemen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to social support having a negative relationship with loneliness, it also has a positive relationship with older adults' physical and mental health (Ermer & Proulx, 2019). Although social network structures change across the life course, older adulthood remains a unique point due to the increased likelihood of experiencing the loss of friends and close family, such as a spouse or romantic partner (Stemen, 2020; Wrzus et al, 2013). This loss can be in the form of death or even divorce, especially considering that the divorce rate is increasing among those over the age 50 (Brown & Lin, 2012).…”
Section: Introductionmentioning
confidence: 99%